Factor influencing online repurchase intention among cosmetic consumers in malaysia - Afiq Khairil Anuar; Fatihatul Najjah Mohd Nor; Liyana Sahira Mohd Zuki; Marina Sudarman (2023)
E-commerce is a growing market, the number of retailers and the growth in online shopping has built up a competitive market. In Malaysia, online repurchasing shows encouraging progress among consumers. The convenience side of online shopping, such as practicality, has strengthened shoppers' intentions to repurchase online. Therefore, this study aims to determine the factors that influence cosmetic consumers’ intention to online repurchase the cosmetic products. This study employed a cross-sectional research design by using a non-probability sampling method. The proposed model is an extension UTAUT and was empirically tested using data obtained from an online survey of online cosmetic shoppers (n=256). A total of 256 data were analyzed using the Statistical Package for the Social Sciences (SPSS). The analysis revealed that security, trust, ease of use, privacy concern and product price has a positive influence on the online repurchase intention among cosmetic consumer. The findings revealed that security had the greatest impact on the intentions to online repurchase among cosmetic consumer. Other theories can be applied to guide future studies to discover more factors that influence online cosmetic shopper to repurchase.